The geometry of Darlington synthesis - Dewilde, Patrick (Zielona Góra: Uniwersytet Zielonogórski)
We revisit the classical problem of 'Darlington synthesis', or Darlington embedding. Although traditionally it is solved using analytic means, a more natural way to approach it is to use the geometric properties of a well-chosen Hankel map. The method yields surprising results. In the first place, it allows us to formulate necessary and sufficient conditions for the existence of the embedding in terms of systems properties of the transfer operation to be embedded.`
Keywords: Darlington synthesis; Hankel operator; time-varying systems; contractive operators; coprime factorization